Analysis of Enterprise Digital Transformation on the Investment Behavior of Institutional Investors: Empirical tests based on multi-period double difference models - Li, Linze (International Journal of Global Economics and Management, 2024)
Serving as a pivotal avenue for fostering seamless integration between the digital economy and the real economy, enterprise digital transformation assumes a pivotal role in shaping a novel development paradigm and advancing the economy towards high-quality growth and as an important part of China's stock market, it is vital to develop the power of institutional investors and guide them to make rational decisions. Considering the characteristics of enterprise digital transformation comprehensively, using the method of financial report mining to measure enterprise digital transformation, and taking A-share listed companies from 2008 to 2021 as sample data, the impact of enterprise digital transformation on the investment behavior of institutional investors is examined by using a multi-temporal DID model. It is found that corporate digital transformation can increase the shareholding ratio of institutional investors.